Influence of external forces on bank recapitalization: an evidence of banks in IMT-GT economic region - Ernovianti, Etri; Ahmad, Nor Hayati (CSRC Publishing, 2017)
Purpose: This paper provides evidence of the influence of selected external forces during the banking crises on the recapitalized performance of banks in Indonesia, Malaysia and Thailand in the IMT-GT economic region.Methodology: The study covers a period of 19 years from 1997 to 2015 across 45 commercial banks.The data was collected from the World Bank database and the global economy website.Results: Although the strategy of capital injection used to strengthen the capital position of the banks proved positively significant, the results showed GDP, Inflation and Political Stability Index had different impact on the recapitalized banks’ performance in these three countries.The overall results appears to indicate that external forces have higher impact on Indonesia banks compared to Thailand and Malaysian banks over the study period. Implications: This study recommend recapitalize banks to efficiently utilize their enlarged capital base to expand their lending activities and investment to real sectors in order to generate higher economic growth for the IMT-GT region.